Tonicia atrata and Chiton cumingsii (Polyplacophora: Chitonidae): First records in European waters - Arias, Andrés; Anadón, Nuria (Zootaxa, 2013)
At present, over 300 species of marine alien Mollusc are reported from the European waters (Streftaris et al. 2005; Zenetos et al. 2010). However, only three alien polyplacophoran have been recorded: Chaetopleura angulata (Spengler, 1797), Acanthopleura gemmata (Blainville, 1825) and Chiton hululensis (E. A. Smith, 1903); the latter is considered as “questionable” (Zenetos et al. 2010). These polyplacophoran constituting about 1% of the alien marine mollusc reported from Europe. Here we present the first record of Tonicia atrata (Sowerby, 1840) and Chiton cumingsii Frembly, 1827 in European waters, constituting the first evidence of their presence outside their native range. Furthermore, we give brief notes on the taxonomy and distribution of T. atrata and C. cumingsii, and discuss the potential pathways for introduction toEurope.